The Influence of Gamification and Customer Experience on Repurchase Intention of Neverdie Store Game Top Up Platform - Ibrahim, Alfalah Zeni Maureno; Junipriansa, Donni; Cahyani, Cahyani (Journal Research of Social Science, Economics, and Management, 2026)
The development of the digital game industry in Indonesia has encouraged the increasing need for game top up services, so that competition between digital platforms is getting tighter. Consequently, this highly competitive environment compels firms to adopt innovative marketing strategies designed to cultivate customer loyalty, notably through the strategic integration of gamification and the rigorous optimization of customer experience management. Addressing this imperative, the present study investigates the structural impact of gamified mechanics and customer experience on the repurchase intentions of users navigating the Neverdie Store, a digital game top-up platform. Employing an explanatory quantitative research design, empirical data were acquired via structured questionnaires from a sample of 100 active platform users and subsequently evaluated utilizing multiple linear regression analysis. The analytical results demonstrate that both gamification and customer experience exert a positive and statistically significant influence on repurchase intention, functioning both independently and concurrently. Furthermore, the coefficient of determination confirms that these dual constructs account for a substantial proportion of the variance in repeat purchasing behavior. Ultimately, these empirical insights underscore that the sophisticated deployment of gamification elements, coupled with superior customer experience management, serves as a vital catalyst for driving sustained repurchase intent within digital marketplaces. Therefore, companies are advised to continue to develop gamification features and improve the quality of customer experience to strengthen user loyalty in the midst of digital platform competition.